Planetaria: Augmented reality-based learning media on solar system lessons for elementary school students - Alief Ya Nur Latifah; Dinn Wahyudin; Effy Mulyasari (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This study aimed to develop Augmented Reality (AR)-based learning media that can assist students in understanding the material on the solar system, specifically the characteristics of the planets within it. This learning media is developed in the form of cards that can be scanned using a smartphone device, with each card displaying a three-dimensional (3D) planet object along with an audio explanation. The research method was Design and Development (D&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results of the study show that the development of the PlanetARia media was validated by system and content experts, with average percentages of 96% and 98%, respectively. The implementation of the PlanetARia media showed positive responses from students regarding visualisation, content, and ease of use. As many as 87% of the students gave very good responses to the media’s visualisation, 73% rated the content aspect as very good, and 83% of the students stated that PlanetARia was easy to use. These results indicate that PlanetARia is visually appealing, content-relevant, and provides ease for students in understanding solar system material.